Proton-Prompted Ligand Exchange to Achieve High-Efficiency CsPbI3 Quantum Dot Light-Emitting Diodes - Li, Yanming; Deng, Ming; Zhang, Xuanyu; Qian, Lei; Xiang, Chaoyu (Nano-Micro Letters, 2024)
CsPbI3 perovskite quantum dots (QDs) are ideal materials for the next generation of red light-emitting diodes. However, the low phase stability of CsPbI3 QDs and long-chain insulating capping ligands hinder the improvement of device performance. Traditional in-situ ligand replacement and ligand exchange after synthesis were often difficult to control. Here, we proposed a new ligand exchange strategy using a proton-prompted in-situ exchange of short 5-aminopentanoic acid ligands with long-chain oleic acid and oleylamine ligands to obtain stable small-size CsPbI3 QDs. This exchange strategy maintained the size and morphology of CsPbI3 QDs and improved the optical properties and the conductivity of CsPbI3 QDs films. As a result, high-efficiency red QD-based light-emitting diodes with an emission wavelength of 645 nm demonstrated a record maximum external quantum efficiency of 24.45% and an operational half-life of 10.79 h. Highlights: 1 A new proton-promoted in situ ligand exchange strategy based on CsPbI3 quantum dots. 2 The ligand exchange strategy maintains the quantum confinement effect of quantum dots and significantly improves the stability and photophysical properties of CsPbI3 quantum dots. 3 The performance of light-emitting diodes based on CsPbI3 quantum dots is significantly improved, the external quantum efficiency is increased from 18.63% to 24.45%, and the half-operational lifetime is increased by 70 times.